PHYTOCHEMICAL PROFILING, ANTIOXIDANT AND CYTOTOXIC ACTIVITY OF TURMERIC-GINGER COMBINATION EXTRACT AGAINST CANCER CELL LINE - Sari Haryanti; Yuli Widiyastuti; Harto Widodo; Rohmat Mujahid; Devi Safrina; Nuning Rahmawati; Dyah Subositi; Wahyu Jokopriyambodo; Sisi Patricia; Steven (Journal of Animal and Plant Sciences, 2025)
Turmeric is recognized for various health benefits, commonly used in nutraceuticals and complementary medicine to alleviate pain and inflammation. It boosts the immune system and is also used for cancer treatment. The challenge in developing of turmeric formulation is the low bioavailability of curcumin as main compound. Literature reviews indicate that ginger is capable of improving blood circulation and enhancing the bioavailability of some compounds, including curcumin. This study aimed to examine the phytochemical profile, cytotoxic activity and antioxidant potential of the turmeric-ginger combination. The extraction was carried out by maceration 3x24 hours using 70% ethanol, evaporated, and dried in the oven. The thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC) were used to obtain phytochemical profiles. Cytotoxic effect was carried out by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT assay). Antioxidant assay was evaluated through H2O2-induced intracellular reactive oxygen species (ROS) quantification using flow cytometer. The HPLC profile revealed that curcumin levels in the turmeric-ginger combination ranged from 6-8%, with gingerol 4-11%.In T47D, HeLa, and WiDr cells, turmeric alone exhibited strong cytotoxicity, while ginger was less effective, and the combination actually reduced cytotoxic effect. However, in HepG2 cells, both turmeric and ginger alone exhibited weak cytotoxicity, surprisingly turmeric-ginger combination 50:50 showed synergistic effect. In Vero cells, ginger 25 and 50 µg/mL demonstrated a more significant capacity to decrease intracellular ROS levels induced by H2O2 when compared to turmeric. The combinations of turmeric ginger 70:30, 60:40, and 50:50 revealed a synergistic effect in reducing ROS levels. This research provides scientific evidence with a synergistic approach supporting the combination of turmeric-ginger to alleviate cancer growth and inhibit ROS generation.
Keywords: turmeric; ginger; formulation; ROS generation; cytotoxic